2023
DOI: 10.3390/antiox12040948
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Determinants, Status, and Antioxidant/Anti-inflammatory-Related Effects in Cardiovascular Risk and Disease: Not the Last Word in the Controversy

Abstract: Beyond its key role in calcium homeostasis, vitamin D has been found to significantly affect the cardiovascular (CV) system. In fact, low vitamin D levels have been associated with increased CV risk, as well as increased CV morbidity and mortality. The majority of effects of this molecule are related directly or indirectly to its antioxidative and anti-inflammatory properties. Generally, vitamin D insufficiency is considered for 25-hydroxyvitamin D (25(OH)D) levels between 21–29 ng/mL (corresponding to 52.5–72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 203 publications
1
25
0
Order By: Relevance
“…Vitamin D can inhibit the NF-κB pathway, potentially suppressing the inflammatory response triggered by TLR activation in AT [ 104 ]. By impeding the phosphorylation and degradation of the IκB protein (inhibitor of kappa B, a protein that binds the NF-κB transcription factor and maintains NF-κB in an inactive state), the 1,25(OH) 2 D 3 -VDR complex hampers NF-κB translocation to the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D can inhibit the NF-κB pathway, potentially suppressing the inflammatory response triggered by TLR activation in AT [ 104 ]. By impeding the phosphorylation and degradation of the IκB protein (inhibitor of kappa B, a protein that binds the NF-κB transcription factor and maintains NF-κB in an inactive state), the 1,25(OH) 2 D 3 -VDR complex hampers NF-κB translocation to the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…The VDR gene encodes the vitamin D receptor, which is involved in lipid metabolism and has been implicated in CAD pathogenesis [ 49 ]. Vitamin D is also thought to have anti‐inflammatory and anti‐atherogenic effects, which may be mediated through the VDR [ 50 ]. The rs2228570 polymorphism is located in the 3′‐untranslated region (UTR) of the VDR gene, which does not affect the protein's amino acid sequence but may affect mRNA stability or translation efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, its levels have shown a correlation with intracranial aneurysm rupture in patients with SAH [ 160 ]. Furthermore, it has been suggested that the vasoprotective effects induced by vitamin D may be attributed to a reduction in oxidative stress [ 161 ]. Nevertheless, its ability to effectively prevent oxidative stress remains inconclusive, and its role as an antioxidant cannot currently be definitively established [ 162 ].…”
Section: Antioxidantsmentioning
confidence: 99%